In vitro gas production and its prediction on metabolize energy of complete feed using rumen fluid of three Indigenous cattle as inoculum taken from abattoir - Rizka Muizzu Aprilia; Shavira Kusherawaty; Hendrawan Soetanto (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2021)
In vitro gas production (IVGP) technique has been routinely used to evaluate the nutritional value of ruminant feed. The pre-requisite of using rumen fluid from fistulae animals is now facing a raising pressure from the animal welfare organization to ban this practice. Alternatively, rumen fluid (RF) from abattoir has been suggested to be used as source of inoculum by a number of scientists. The objective of this study was to evaluate the potential of rumen fluid taken from cattle that were slaughtered at Surabaya abattoir as inoculum for IVGP measurement and its prediction on metabolic energy (ME) of a complete feed. Fresh rumen fluid of three indigenous cattle, namely Ongole Cross Breed (OCB), Madura (MC) and Bali Cattle (BC) was transferred into a vacuum thermo flask and immediately transported to the animal nutrition laboratory of Brawijaya University for further processes to measure IVGP of complete feed in a completely randomized block design with two replicates each. Gas production was monitored at time intervals and terminated after 48 hours incubation in the oxygen-free glass syringes at 38°C. Feed degradability was calculated by gravimetric method at 48 hours, while prediction of ME content was based on 24 h GP and estimated using the equation described by Menke and Steingass (1979).The results demonstrated that inoculum from OCB resulted in the superiority in all parameters, namely total GP (ml/500 mg DM), potential of GP (ml/500 mg DM), rate constant of gas production for insoluble fraction (ml/hour), and estimated ME content (MJ/DM) compared with MC and BC. Based on these findings it can be concluded that the fermentation process of complete feed in the rumen of OCB is more efficient than MC and BC which reflects to the more efficient interaction among rumen microbes to ferment the feed ingredients.